2010
DOI: 10.1039/b922220k
|View full text |Cite
|
Sign up to set email alerts
|

Solvent induced shape recovery of shape memory polymer based on chemically cross-linked poly(vinyl alcohol)

Abstract: A shape memory polymer based on poly(vinyl alcohol) (SM-PVA) chemically cross-linked with glutaraldehyde exhibits good temperature responsive shape memory behavior. In the present investigation, solvent-induced shape memory behavior is observed by immersing this kind of SM-PVA in good or poor solvents (including water, DMF, and EG etc.) for PVA. A significant indication of shape memory is the decrease of the glass transition temperature (T g ), which is caused by PVA swelling in certain solvents. Differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
185
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(195 citation statements)
references
References 55 publications
(51 reference statements)
9
185
1
Order By: Relevance
“…Recent studies have shown that environmental conditions, such as the humidity, can substantially influence the conformational mobility of macromolecular chains and, thus, the shape memory properties of some polymers [2][3][4]. These findings motivated the development of the concept of a moisture-triggered shape memory effect.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that environmental conditions, such as the humidity, can substantially influence the conformational mobility of macromolecular chains and, thus, the shape memory properties of some polymers [2][3][4]. These findings motivated the development of the concept of a moisture-triggered shape memory effect.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, we have seen great efforts in developing new polymers and improving existing ones for tailored shape memory features, improved performance and/or new functions [14,29,34,37,52,55,79,[131][132][133][134][135][136][137][138][139][140][141][142][143][144][145]. On the other hand, the SME has been discovery in many other materials beyond the traditional polymers, such as starch, maize flour and even nails [3,146].…”
Section: Design Of Polymeric Materials and Optimizationmentioning
confidence: 99%
“…This is another major advantage of this hybrid concept. This concept can be easily extended into solventresponsive shape memory hybrids [28], in which a particular chemical is the stimulus to trigger the shape recovery or other means of mechanical action. Consequently, targeted drug release can be more conveniently (or even routinely) realized.…”
Section: Discussionmentioning
confidence: 99%